Cost efficiency of French commercial banks: a stochastic frontier analysis - Cai, Sihui (2019)
This paper estimates cost efficiency and potential determinants of cost efficiency by using the sample of 40 commercial banks in France from 2011 to 2018. Two main stages are contained in this study. In the first step, stochastic frontier approach (SFA) is adopted to assess efficiency scores of banks. The results show the fluctuating trend of cost efficiency for French banking sector with an average of 87.45% for the overall period. Moreover, it also found that foreign banks in France are more efficient than domestic banks at first while the efficiency level of domestic banks exceeds those of foreign banks from 2016. In the second step, five bank-specific variables are selected to explore determinants of bank efficiency by employing Panel Tobit regression model. The findings provide a suggestive inference that the variables including SIZE, LOANS as well as EQUITY have a significant positive correlation with cost efficiency, whereas LLPGL and ROAA are negatively correlated.